Occurrence of antibodies anti-Toxoplasma gondii among sheltered and free-roaming cats within a university campus - Kmetiuk, Louise Bach; Pellizzaro, Maysa; Yamakawa, Ana Carolina [UNESP]; Mendes, Juliana Cristina Rebonato; Martins, Camila Marinelli; Canavessi, Aurea Maria Oliveira; Langoni, Helio [UNESP]; dos Santos, Andrea Pires; Biondo, Alexander (Universidade Estadual de Londrina, 2021)
The present study aimed to assess anti-T. gondii antibodies in sheltered and free-roaming cats within a university campus that has an overlapping population of humans and livestock. A total of 51 cats were tested for anti-T. gondii antibodies using the indirect immunofluorescent antibody test. Overall, 8/51 cats (15.7%) were seropositive. Cats were more likely to be seropositive when free-roaming (p= 0.008) and with presence of skin lesions (p= 0.042), and less likely with < 1 year of age (p= 0.021), probably due to higher environmental exposure and infected prey consumption. The presence of seropositive free-roaming cats whose areas overlapped those occupied by humans and livestock may suggest an increased on-campus chance of T. gondii occurrence.
Ocorrência de anticorpos anti-Toxoplasma gondii entre gatos de abrigo e de vida livre dentro de um campus universitário
Keywords: Associated factors; Feral cats; Toxoplasmosis